The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1751-7915.13032
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fluidification by ethanol stress activates unfolded protein response in yeasts

Abstract: SummaryThe toxic effect of ethanol is one of the most important handicaps for many biotechnological applications of yeasts, such as bioethanol production. Elucidation of ethanol stress response will help to improve yeast performance in biotechnological processes. In the yeast Saccharomyces cerevisiae, ethanol stress has been recently described as an activator of the unfolded protein response (UPR), a conserved intracellular signalling pathway that regulates the transcription of ER homoeostasis‐related genes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…Ethanol tolerance is a complex phenotype, and different mechanisms may lead to improved tolerance. Fluidisation of the yeast membranes by ethanol is also known to activate the unfolded protein response (UPR), and it is speculated that a better response could lead to greater on April 4, 2021 by guest http://aem.asm.org/ Downloaded from tolerance (52). Moreover, yeast cells can increase their tolerance to ethanol by other mechanisms, such as the increase the biosynthesis of some amino acids, as tryptophan (53) and trehalose accumulation (54).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol tolerance is a complex phenotype, and different mechanisms may lead to improved tolerance. Fluidisation of the yeast membranes by ethanol is also known to activate the unfolded protein response (UPR), and it is speculated that a better response could lead to greater on April 4, 2021 by guest http://aem.asm.org/ Downloaded from tolerance (52). Moreover, yeast cells can increase their tolerance to ethanol by other mechanisms, such as the increase the biosynthesis of some amino acids, as tryptophan (53) and trehalose accumulation (54).…”
Section: Discussionmentioning
confidence: 99%
“…Physical and chemical factors affecting protein functions will affect the activity of enzymes; for example, high temperatures, strong acids, and strong bases can cause a loss of catalytic ability. Studies on other strains have shown that increased temperatures and other stresses (for example, ethanol stress) could lead to a number of changes, including protein denaturation, DNA damage, cell cycle arrest, and changes in the fluidity of the membrane 33 . One of the most deleterious factors in stressed cells is the disturbance (unfolding) of the protein structure, which leads to protein aggregation, thus affecting the functionality 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, little is known about how lipids modulate various biological mechanisms in yeast cells during beer fermentation besides affecting membrane structure and/or permeability. However, it is known that membrane fluidification by ethanol can activate the endoplasmic reticulum (ER)-5 linked unfolded protein response (UPR) (Navarro-Tapia et al, 2018) and lipids may have other roles in proteostasis, such as the removal of unfolded proteins from the ER by lipid droplets (LDs) (Vevea et al, 2015). LDs are important and highly dynamic cytoplasmic organelles that connect different parts of the cell, including the ER (Jacquier et al, 2011), mitochondria (Pu et al, 2011), peroxisomes (Kohlwein et al, 2013), and vacuoles (Barbosa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%